A model to investigate extraction parameters for anthocyanin from Melastoma malabathricum - Aziz, N.; Arof, Abdul Kariem (Springer, 2016)
The study comprises the design of an experimental model to investigate the parameters for anthocyanin extraction from Melastoma malabathricum on CIE color responses. Extractions have been carried out using acidified methanol solvent at 30 and 80°C, soaking time 60 and 180 min and trifluoroacetic acid content of 0.5 and 3 %. Analysis of variance was chosen to evaluate significance of the model. In this study interaction between TFA content with soaking time has the highest significance effect on CIE color parameters study mentioned above. The optimized parameters are 0.5 % TFA content, soaking time 132.43 min and extraction temperature 80°C.